Abnormal chromatin clumping in leucocytes of Ph positive Chronic Myeloid Leukemia cases - extending the morphological spectrum - Adhya Amit; Ahluwalia Jasmina; Varma Neelam; Das Reena; Varma Subhash (Wolters Kluwer Medknow Publications, 2008)
The syndrome of abnormal chromatin clumping is largely a morphological entity characterized by exaggerated chromatin clumping seen in the neutrophils. According to the recent World Health Organization (WHO) classification, it is categorized as a variant of atypical chronic myeloid leukemia (aCML) or Ph-negative CML. Most of the cases reported in literature have been negative for the Ph chromosome or the BCR-ABL gene. Till date, Ph positivity has been demonstrated in just one case. We report two more Ph-positive CML cases with abnormal chromatin clumping in neutrophils. To the best of our knowledge, this is only the second time in literature that such cases have been described. These two unusual cases go on to extend the morphological spectrum of granulocytic changes seen in Ph-positive CML.